An in vitro study of neutrophil chemotaxis - Todd, Gail (Department of Human Biology, 2020)
When, at the beginning of 1972, my scientific attention was first drawn to the subject of cellular participation in the inflanunatory response, I was struck by the need for an understanding of the cellular and molecular mechanisms whereby blood leucocytes are attracted to an area of injury. The literature at that time contained good technical accounts of methods available for studying chemotaxis in vitro and many reports of diverse compounds of biological origin with attractant, or chemotactic, properties for motile, phagocytic cells. In general, these reports tended to substantiate the belief that chemical substances generated at an inflannnatory source attracted cells to that source in a teleologically appropriate way and they justified, by the consistent correlation observed, the relevance of in vitro procedures for studying the phenomenon. In other words, answers were available to the question "What substances attract?"; very few were available to the question, "How do they attract?".